2015
DOI: 10.1007/s00432-015-1925-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of transcription factor Fra-1 in ER-positive breast cancer: contribution to a metastatic phenotype through modulation of tumor cell adhesive properties

Abstract: Thus, in addition to its pro-invasive and pro-migratory effect, Fra-1 might influence the metastatic potential of breast cancer cells by changing the expression of adhesion molecules, resulting in increased adherence to endothelial cells under flow conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…High levels of Fra-1 in cells where elevated ERK activity leads to protein stabilization provide survival signals for tumor cells removed from the extracellular matrix (31). Fra-1 may influence the metastatic potential of breast cancer cells by altering the expression of adhesion molecules, resulting in increased adherence to endothelial cells under flow conditions (32). Collectively, the results suggested that Fra-1 may affect cell proliferation, invasion and apoptosis.…”
Section: Discussionmentioning
confidence: 94%
“…High levels of Fra-1 in cells where elevated ERK activity leads to protein stabilization provide survival signals for tumor cells removed from the extracellular matrix (31). Fra-1 may influence the metastatic potential of breast cancer cells by altering the expression of adhesion molecules, resulting in increased adherence to endothelial cells under flow conditions (32). Collectively, the results suggested that Fra-1 may affect cell proliferation, invasion and apoptosis.…”
Section: Discussionmentioning
confidence: 94%
“…High AP-1 expression is associated with poor prognosis of breast cancer. For example, analysis of cDNA microarray data including 197 breast cancer patients showed that high expression of Fra-1 significantly correlates with shorter overall survival and higher percentage of lung metastasis in ERα-positive breast cancer patients [215]. Moreover, a role for Fra-1 or c-Jun in promoting breast cancer cell metastasis in vivo has been demonstrated in a zebrafish tumor xenograft model [214], and Fra-1 has been identified as a key regulator involved in the process of metastasis in rodent model systems [216].…”
Section: The Role Of Ap-1 In Breast Cancermentioning
confidence: 99%
“…Fra-1 is required for invasion and Fra-1 might be a good target for intervention in colorectal cancer (3,5,6). In addition to its pro-invasive and pro-migratory effect, Fra-1 might influence the metastatic potential of breast cancer cells by changing the expression of adhesion molecules, resulting in increased adherence to endothelial cells (1,7,8). Although some evidence has been reported, the mechanism of Fra-1 in malignancy is not fully understood.…”
Section: Introductionmentioning
confidence: 99%